Financial reputation, market interventions and debt issuance by banks: a truncated two-part model approach - Gonzalo Camba-Méndez; Santiago Carbó-Valverde; Diego Rodriguez-Palenzuela (European Central Bank (ECB), 2014)
In this paper we study the impact that financial reputation and official market interventions have on the timing and amount of debt issuance decisions by banks. To do so, we propose an extension of the two-part modelling framework of Cragg (1971, eq. 7 and 9) to accommodate random effects. We use quarterly information on 70 major listed European banks from 2003Q1 to 2012Q1. Focusing on a wide range of financial reputation indicators, we show that credit ratings are a significant and positive determinant of the timing of uncollateralised debt issuance decisions. Empirical results do not suggest that ratings have a significant impact on the amount of debt placed by banks. Other financial reputation indicators analysed are found to be of second- order relevance on debt issuance decisions. Our results also suggest that central bank liquidity programs may have had a large impact on both the timing and the amount of collateralised debt issuance during the recent financial crisis, but had a negligible impact on uncollateralised debt issuance decisions.
Keywords: G21; G01; G15; 330; bank debt issuance; collateral; crisis; monetary policy